Current developments in the production of fungal biological control agents by solid-state fermentation using organic solid waste. Issue 8 (18th April 2019) - Sala, Arnau; Barrena, Raquel; Artola, Adriana; Sánchez, Antoni
Abstract: Biological control agents are slowly and steadily replacing traditional chemical pesticides. Among them, fungal entomopathogens have assumed a key role in controlling a growing number of pests. Research on fungal entomopathogens has expanded constantly during the last decades, confirming real interest in their biocontrol potential. The production of fungal entomopathogens by solid-state fermentation has arisen as a sustainable production method, which is slowly becoming preferred over submerged fermentation considering the advantage of using of agro-industrial wastes as substrates. This review discusses relevant studies on fungal entomopathogens, with a special interest in their production as biocontrol agents by solid-state fermentation processes, including reactors used and operational conditions, focusing mainly on the two most-used fungal entomopathogens worldwide, Beauveria spp. and Trichoderma spp.